2009
DOI: 10.1073/pnas.0909545106
|View full text |Cite
|
Sign up to set email alerts
|

A selective contribution of the RIG-I-like receptor pathway to type I interferon responses activated by cytosolic DNA

Abstract: The activation of the innate immune responses by DNA exposed within the cytosol has gained much attention and, in this context, several cytosolic DNA sensors have been identified. However, previous studies revealed the operation of redundant and complex mechanisms and it still remains to be clarified how the DNAmediated evocation of diverse innate immune responses can be achieved. Here we show that two RIG-I-like receptors (RLRs), RIG-I and MDA5, known as cytosolic RNA receptors, nonredundantly function as cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 33 publications
(49 reference statements)
2
79
1
Order By: Relevance
“…RIG-I recognizes a wide variety of RNA viruses, whereas MDA5 recognizes mainly picornaviruses whose RNAs do not bear 59-triphosphates (32,37). Intriguingly, several recent studies have revealed that RIG-I and MDA5 are able to induce an antiviral response to viruses containing dsDNA genomes, such as EBV (52,53), vaccinia virus (51, 54), and HSV (55,56). RIG-I is proposed to induce an antiviral response to DNA viruses via RNA poly- merase III-mediated conversion of microbial DNA into 59-triphosphate dsRNA (57,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RIG-I recognizes a wide variety of RNA viruses, whereas MDA5 recognizes mainly picornaviruses whose RNAs do not bear 59-triphosphates (32,37). Intriguingly, several recent studies have revealed that RIG-I and MDA5 are able to induce an antiviral response to viruses containing dsDNA genomes, such as EBV (52,53), vaccinia virus (51, 54), and HSV (55,56). RIG-I is proposed to induce an antiviral response to DNA viruses via RNA poly- merase III-mediated conversion of microbial DNA into 59-triphosphate dsRNA (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…RIG-I is proposed to induce an antiviral response to DNA viruses via RNA poly- merase III-mediated conversion of microbial DNA into 59-triphosphate dsRNA (57,58). Recognition of the DNAs of HSV and EBV by RIG-I is mediated via this pathway (52,55,58). Of note, one report showed that innate recognition of HSV in macrophages is mediated via an MDA5-dependent and RNA polymerase III-independent pathway (56).…”
Section: Discussionmentioning
confidence: 99%
“…During microbial infection or tissue damage, DNA and RNA potently activate the innate and subsequent adaptive immune responses. In mammals, the transmembrane PRR Toll-like receptor (TLR)3, TLR7, and TLR9, respectively, recognize double-stranded RNA, single-stranded and short double-stranded RNAs, and hypomethylated DNA, whereas retinoic acid-inducible gene I (RIG-I)-like receptors, namely RIG-I and melanoma differentiation-associated gene 5 (MDA5), are best known as RNA-sensing receptors in the cytosol, but more recently have been shown to also participate in the cytosolic DNA-sensing system (5)(6)(7)(8). In addition, cytosolic DNA-sensing receptors, which include DNA-dependent activator of IFN regulatory factors (IRFs) (DAI), absent in melanoma 2 (AIM2), among others, have been identified (9, 10).…”
mentioning
confidence: 99%
“…The reduced IFN- level in Sting -/-MEFs to synthetic poly(dA:dT) dsDNA was accounted for an additional Type I IFN response that is independent of both TLR and STING, and mediated by the dsDNA induced innate immune signalling receptor RIG-1 [60]. RIG-1, a member of the RLR family, is a dsRNA receptor that also triggers antiviral response to dsDNA [186][187][188] . …”
Section: Stingmentioning
confidence: 99%